Investigation of activation energy and antibacterial activity of CuO nano-rods prepared by Tilia Tomentosa (Ihlamur) leaves - Shashanka, R.; Yılmaz, Volkan Murat; Karaoğlanlı, Abdullah Cahit; Uzun, Orhan; Yılmaz, Volkan Murat; Karaoğlanlı, Abdullah Cahit (Univ Mohammed Premier Oujda, 2020)
In recent years, fabrication of metal oxide nanoparticles is intensively gained the interest of various chemists as well as biochemist due to their wide range of applications in different fields. Therefore, we reported an easy and eco-friendly synthesis of CuO nano-rods by using Tilia Tomentosa (Ihlamur) leaves extract. Producing CuO nanoparticles exhibiting rod-like shape is rare and difficult using plant leaves, but it is possible using tilia leaves. The green synthesized CuO nano-rods were calcined at 400 degrees C for 15 minutes and were characterized by UV-Visible spectroscopy, XRD, SEM and particle size analyzer to study their bandgap, phases, shape and sizes respectively. SEM studies reveal the formation of rod-shaped CuO nanoparticles with an average length of 95nm and that of breadth is 32nm. Further, the thermal properties of CuO nano-rods were studied by using TG and DTA analysis. Thermal studies were carried out at 6, 8 and 10 degrees/min heating rates to study the enthalpy and activation energy in detail. The activation energy of CuO nano-rods was calculated by the Kissinger method and was found to be 12.23 kJ/mol. Antibacterial activity of CuO nano-rods was carried out using S. aureus, P. flourescens, E. faecalis, B. subtilis, S. enteridis and E. coli.
Keywords: Cuo Nano-Rods; Tilia Tomentosa; Green Synthesis; Uv-Visible Spectroscopy; Activation Energy; Antibacterial Activity